Lago-Na! promoting the continuity of Laguna de Bay - Enriquez, Nika Soleil U.; Gines, Leonido Jr. (Quezon City College of Architecture, University of the Philippines Diliman, 2022)
Laguna de Bay is the largest lake in the Philippines and one of the country's most important freshwater resources. It supports a number of uses such as irrigation, drinking water, and most prominently, aquaculture. However, people's economic success with and dependence on the lake introduced more settlements by the waters that are disconnected to the environment itself thus engage in detrimental activity such as waste dumping. This is exacerbated by climate change that has also been prompted by the economic growth. The lake's degradation affects the integrity of existing activities and industries, especially the fisheries. In pursuit of improving the lake's situation, this project takes on an approach to involve the communities with the closest relationship to the resource, the fisherfolk. Studies on resource management and stakeholder involvement show that people feel disconnected to the lake due to improvement programs catering to government, corporations, or other people who are not the stakeholders themselves. However, these stakeholders have the most potential to maintain resources as they are the most affected by the detriment and also benefit the most from positive change. With this, the project explores developing an architectural intervention that promotes the continuity of the lake by encouraging community resource management through socioeconomic development and positive experiences. It seeks to be an immersive water-based intervention that provides a physical avenue in which the stakeholders can convene, learn, work, and be inspired to use their expertise to move forward in harmony with the lake and promote its continuity into the future.
includes appendices
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Laguna de Bay; Natural resources -- Management; Lake degradation